Manejo da lâmina e supressão da irrigação e da frequência de fertirrigação potássica na cultura da soja - Amaral Neto, Abelardo Lopes (2017)
In modern production systems, such as soybean production, one wants to maximize the efficiency of using the production inputs to achieve high productivity and cost reduction in a sustainable way. To achieve this goal, especially in regions characterized by scarcity of water resources, such as the state of Ceará, the use of more efficient irrigation systems and the adoption of efficient water and nutritional management of the crop are essential. Therefore, the objective of this work was to study the effects of irrigation slides, irrigation suppression moments and potassium fertirrigation frequencies in the soybean crop, under the edaphoclimatic conditions of Ceará. The experiments were carried out in the experimental area of the Agrometeorological Station, Federal University of Ceará, in the city of Fortaleza, Ceará. The experimental design was a randomized block design, with six treatments and four replications for the experiment with irrigation slides. For the other experiments, five treatments and four replications were used. In the first experiment, treatments were irrigation slides corresponding to six percent crop evapotranspiration (ETc): 25; 50; 75; 100; 125; and 150% of ETc during the cycle. In the second experiment, the treatments were five moments of suppression of the irrigation blade: 50; 60; 70; 80; and 90 days after planting. In the third experiment, the treatments were five frequencies of potassium fertirrigation: 2; 4; 8; 16; and 32 fertigations at the recommended dose per cycle. The analyzed variables were: height of the plant; height of the first pod; number of pods per plant; stem diameter; fresh and dry pasta of the aerial part; and grain yield. According to the results, the irrigation depth estimated with 150% of ETc maximizes grain yield. The moments of suppression of irrigation influence the number of pods per plant, but without interfering with the yield components. The frequency of potassium fertirrigation does not interfere with the yield components of the grains.